Zero-Waste Garment Pattern Cutting as a Sustainable Practice for Garment Construction Students in Tertiary Institutions in Lagos State, Nigeria - Owodiong-Idemeko, Boiso Maria; Idowu, Samson Adeshola; Ogundele, Atinuke Dorcas; Kaka, Bailikis Omolade (NIU Journal of Educational Research, 2025)
The study was on Zero Waste Garment Pattern Cutting as a Sustainable Practice for Garment Construction Students in Tertiary Institutions in Lagos State, Nigeria. The area of study was Lagos State. Among three tertiary institutions in the state. Lagos State University of Education, Oto, Ijanikin, Yaba College of Technology, and University of Lagos, Yaba. The study design was a descriptive survey. Two objectives, two research questions, and two hypotheses guided the research. A questionnaire was the main instrument used for the study, containing 35 questions and a three-point Likert scale. Results reveal that out of 150 students, 123 (82) answered yes, wastes are created at every stage of garment construction. 132 (88) answered yes, this is as a result of irregular shape of pattern pieces. 150 (100) answered yes, student pattern makers need to be artistic by using creativity and ingenuity to eliminate waste. 86 (57) answered yes, students need to eliminate waste by drafting simple styles. 150, (100) answered yes, waste, if not properly handled or disposed of, pollutes the environment. 150 (100) answered yes, waste created in the cutting room can be converted to something new to create jobs. 132 (88) answered yes, working with design dimensions while sourcing for textiles prevents waste. 106 (71) answered yes, this prevents unnecessary embellishment. 141(94) answered yes, these practices are sustainable. In conclusion, zero-waste pattern cutting is a sustainable practice. Therefore, simple styles combined with creativity and ingenuity is recommended. Keywords: Garment construction, garment pattern cutting, students, sustainable practices, tertiary institutions, zero waste.